The research for various genotypes and phenotypes related to rare -90 (C>T) β-thalassemia mutation in Ganzhou city, Southern China - Zhang, Hui-Juan; Hu, Xiao-Mei; Liu, De-Dong (Frontiers in Hematology, 2023)
Thalassemia is a heterogeneous group of genetic disorders affecting the hemoglobin genes leading to decrease synthesis of globin chains of hemoglobin and resulting in ineffective erythropoiesis. It usually contains α- and β-thalassemia, most of common mutation types of which can be detected. However, it’s inclined to miss rare thalassemia mutation types. Here, we analyzed the molecular and hematological characteristics of seven cases with rare β-thalassemia -90 (C>T) (HBB: c.-140 C>T) mutation. Five of them carried β-90 (C>T) heterozygous mutation with a β+ thalassemia trait. One case was αSEA/β-90 genotype with decreasing MCV and MCH obviously, and the other was a β+/β0 intermediate thalassemia patient with β-90/βCD17 genotype, presenting with moderate anemia. A pedigree of one case was analyzed subsequently. It was found that the proband's maternal grandfather and mother were carriers of α3.7/β-90 double heterozygous thalassemia, who presented that MCV and MCH were decreased normally or slightly, and HbA2 was increased. The proband and his aunt were β-90 (C>T) carriers. It’s necessary to point that the MCV and MCH were much higher in carrier of α3.7/β-90 genotype compared with either αSEA/β-90 genotype or β-90 heterozygous mutation. In this study, we explore the genotypes and phenotypes of four diverse β-90、αSEA/β-90、α3.7/β-90、β-90/βCD17 thalassemia mutations, which enriches the gene profile of β-thalassemia mutation in Chinese population.